Completed secondary education among youth with prenatal substance exposure: A longitudinal register-based matched cohort study - Nissinen Niina-Maria; Gissler Mika; Sarkola Taisto; Kahila Hanna; Autti-Rämö Ilona; Koponen Anne M (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2025)
Introduction: The dual impact of prenatal substance exposure (i.e. alcohol/drugs) and adverse postnatal caregiving environment on offspring secondary education completion is an understudied research area. The aim was to investigate the influence of childhood adversities, out-of home care, and offspring's mental and/or behavioural disorders on secondary education completion among prenatally exposed offspring in comparison to matched unexposed offspring.
Methods: This is a longitudinal register-based matched cohort study in Finland including offspring with a history of prenatal substance exposure and a matched unexposed cohort. The study sample included 283 exposed and 820 unexposed offspring aged 18-23 years.
Results: The results showed a time lag in secondary education completion and lower educational attainment overall among exposed compared with unexposed (37.8% vs. 51.0%, respectively). The results from the multivariate logistic regression models showed that the differences in the secondary education completion between exposed and unexposed were diminished in the presence of covariates. A cumulative childhood adversity score and out-of-home care were not associated with secondary education completion in the multivariate models, whereas the different domains of offspring's mental and/or behavioural disorders including psychiatric disorders (AOR 0.65, 95% CI 0.45-0.96), neuropsychological disorders (AOR 0.35, 95% CI 0.23-0.54) and dual psychiatric and neuropsychological disorder (AOR 0.29, 95% CI 0.18-0.48) showed an independent negative effect on secondary education completion.
Conclusions: Inferior educational outcomes may not be directly linked with prenatal substance exposure but may rather reflect the extent of evolving offspring's mental and/or behavioural disorders over time influenced by childhood adversities.